509 Microenvironmental Characteristics of Growing and Static Vestibular Schwannomata. (1st April 2022) - Hannan, Cathal; Lewis, Daniel; MacArthur, Joshua; Cooper, Christopher; Hammerbeck-Ward, Charlotte; Rutherford, Scott A.; Lloyd, Simon K.; Freeman, Simon R. M.; Coope, David J.; Pathmanaban, Omar N.; Roncaroli, Federico; King, Andrew
Abstract : INTRODUCTION: Vestibular schwannomas (VS) display a wide variation in their natural history, with ∼60% exhibiting progressive growth, while the remainder do not grow. There is emerging evidence that the tumor microenvironment (TME) plays a central role in driving tumour growth. Previous studies in this area have been limited by small sample sizes, a shortcoming we addressed in the present study. METHODS: We identified 120 patients with sporadic VS from a prospectively maintained database. 100 consecutive growing cases and 20 consecutive static cases were included. Tumour volumes and growth rates were established by analysis of MR imaging using Brainlab Elements TM . Tumour tissue was analysed using immunohistochemistry to assess for macrophage infiltrates (Iba1), microvessel surface area (CD31) and vascular permeability (Fibrinogen). Immunostains were quantified using ImageJ (www.imagej.nih.gov ). Statistical analysis was performed using the appropriate non-parametric tests. RESULTS: The mean Iba1+ macrophages was significantly higher in growing VS when compared to static VS (591 vs. 317/x20 HPF, p=0.02). Growing VS also had a significantly higher microvessel surface area than static VS (2.16% vs. 1.37%, p=0.032), as well as higher vascular permeability as assessed by optical density of fibrinogen staining (0.64 vs. 0.45, p=0.038). There was a statistically significant correlation between tumour macrophage infiltration and tumour vascularity (rs=0.4189, p=<0.001). CONCLUSION: We documented marked differences in the TME of growing and static VS, validating our previous observation. Growing VS exhibited higher macrophage density, increased vascularity and higher vascular permeability. Targeting these processes may yield therapeutic benefit for patients with sporadic and neurofibromatosis type 2 related VS.